Dynamic Changes of Ocular Surface in First-Time Contact Lens Wearers and the Effective Factors of Contact Lens Discomfort - Xu, Yangyang; Xu, Zhiqiang; Shu, Xupeng; Liu, Qiaoli; Wang, Yuzhou; Xia, Jiahui; Li, Yong; Qu, Jia; Hu, Liang (Frontiers in Medicine, 2022)
Purpose The purpose of the study is to investigate the dynamic changes in ocular surface indicators in first-time contact lens (CL) wearers and identify the most influential factors in CL discomfort (CLD). Methods A total of 26 healthy non-CL wearers (26 eyes) were recruited and fitted monthly with disposable hydrogel CLs. Each participant underwent a full ocular surface evaluation, which include Efron grading, tear film breakup time, Schirmer's I test, corneal dendritic cell (DCs) imaging by in vivo confocal microscopy (IVCM), and conjunctival microvasculature evaluation by functional slit-lamp biomicroscopy. CLD was assessed using the Ocular Surface Disease Index questionnaire at baseline, 1 week, 1, 3, and 6 months after wearing it and another 6 months after discontinuing it. Results Clinical signs and CLD were significantly increased in the first week (p < 0.05). The microvascular response and DC activation peaked at the 1-month interval (p < 0.05). During CL wear, CLD is positively correlated with corneal staining (B = 0.238, p = 0.002), papillary conjunctivitis (B = 0.245, p < 0.001), and microvascular blood flow velocity (B = 0.353, p < 0.001). After discontinuation, only DC activation remained elevated at 6 months, whereas the other signs recovered. Conclusions The first week of CL wear was the main period for the appearance of ocular surface clinical signs, and the first month was the main period for the activation of subclinical inflammation. Corneal staining and conjunctival microvascular response are the main factors affecting CLD. Even if the clinical signs recover after discontinuing wear, subclinical inflammation may persist.